Unusual osseous presentation of blastomycosis in an immigrant child: a challenge for European pediatricians - Codifava Margherita; Guerra Azzurra; Rossi Giulio; Paolucci Paolo; Iughetti Lorenzo (BMC, 2012)
Abstract Background Blastomycosis, caused by the thermally dimorphic fungus Blastomyces dermatitidis is a systemic pyogranulomatous infection, endemic in United States and Canada, with few reported cases in Africa and Asia. It is uncommon among children and adolescents, ranging from 3% to 10%. Clinical features vary from asymptomatic spontaneously healing pneumonia, through acute or chronic pneumonia, to a malignant appearing lung mass. Blastomycosis can originate a "metastatic disease" in the skin, bones, genitourinary tract and central nervous system. Bone is the third most common site of blastomycotic lesions, after lung and skin. Bones may be involved in 14-60% of cases of blastomycosis. Direct visualization of single broadbased budding yeast with specific stains in sputum or tissue samples at microscopy is the primary method for diagnosis, while culture is timeconsuming and other methods are unreliable. Case presentation We report a case of severe osteoarticular Blastomycosis occurring in a 3-years-old presented to our Emergency Department with pain and swelling of the left knee, successfully treated with surgical curettage and antifungal therapy. To our knowledge this is the first case reported in Europe. Conclusions Blastomycosis represents a challenge for European physicians, and it should be included in the differential diagnosis of unexplained infections in patients coming from endemic areas.